Lysosome and Inflammatory Defects in GBA1‐Mutant Astrocytes Are Normalized by LRRK2 Inhibition. Issue 5 (8th February 2020) - Sanyal, Anwesha; DeAndrade, Mark P.; Novis, Hailey S.; Lin, Steven; Chang, Jianjun; Lengacher, Nathalie; Tomlinson, Julianna J.; Tansey, Malú G.; LaVoie, Matthew J.
Abstract: Background: Autosomal recessive mutations in the glucocerebrosidase gene, Beta‐glucocerebrosidase 1 ( GBA1 ), cause the lysosomal storage disorder Gaucher's disease. Heterozygous carriers of most GBA1 mutations have dramatically increased Parkinson's disease (PD) risk, but the mechanisms and cells affected remain unknown. Glucocerebrosidase expression is relatively enriched in astrocytes, yet the impact of its mutation in these cells has not yet been addressed. Objectives: Emerging data supporting non‐cell‐autonomous mechanisms driving PD pathogenesis inspired the first characterization of GBA1 ‐mutant astrocytes. In addition, we asked whether LRRK2, likewise linked to PD and enriched in astrocytes, intersected with GBA1 phenotypes. Methods: Using heterozygous and homozygous GBA1 D409V knockin mouse astrocytes, we conducted rigorous biochemical and image‐based analyses of lysosomal function and morphology. We also examined basal and evoked cytokine response at the transcriptional and secretory levels. Results: The D409V knockin astrocytes manifested broad deficits in lysosomal morphology and function, as expected. This, however, is the first study to show dramatic defects in basal and TLR4‐dependent cytokine production. Albeit to different extents, both the lysosomal dysfunction and inflammatory responses were normalized by inhibition of LRRK2 kinase activity, suggesting functional intracellular crosstalk between glucocerebrosidase and LRRK2 activities in astrocytes. Conclusions: These data demonstrate novel pathologic effects of a GBA1 mutation on inflammatory responses in astrocytes, indicating the likelihood of broader immunologic changes in GBA‐PD patients. Our findings support the involvement of non‐cell‐autonomous mechanisms contributing to the pathogenesis of GBA1 ‐linked PD and identify new opportunities to correct these changes with pharmacological intervention. © 2020 International Parkinson and Movement Disorder Society